2009
DOI: 10.1016/j.icarus.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Mg-rich carbonates on Mars from a 3.9 μm absorption feature

Abstract: Evidence for Mg-rich carbonates on Mars from a 3.9 μm absorption feature, Icarus (2009Icarus ( ), doi: 10.1016Icarus ( /j.icarus.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Until recently these proposals were motivated by the lack of detection of massive carbonates (e.g., Bullock and Moore, 2007;Chevrier et al, 2007) that would be present under a CO 2 -rich atmosphere with liquid water stable on the surface (Schaefer, 1993). Evidence from several groups (Ehlmann et al, 2008;Boynton et al, 2009;Palomba et al, 2009;Michalski and Niles, 2010;Morris et al, 2010) has shown that there are carbonates previously undiscovered on Mars, though it remains unclear whether the mass of these carbonates is sufficient to account for a substantial early CO 2 greenhouse.…”
Section: Other Greenhouse Gases?mentioning
confidence: 99%
“…Until recently these proposals were motivated by the lack of detection of massive carbonates (e.g., Bullock and Moore, 2007;Chevrier et al, 2007) that would be present under a CO 2 -rich atmosphere with liquid water stable on the surface (Schaefer, 1993). Evidence from several groups (Ehlmann et al, 2008;Boynton et al, 2009;Palomba et al, 2009;Michalski and Niles, 2010;Morris et al, 2010) has shown that there are carbonates previously undiscovered on Mars, though it remains unclear whether the mass of these carbonates is sufficient to account for a substantial early CO 2 greenhouse.…”
Section: Other Greenhouse Gases?mentioning
confidence: 99%
“…Carbonate detections using features in the 4-mm region are possible to abundances as low as o $ 5% for even weakly-featured carbonates (i.e., magnesite and huntite) when these carbonates are mixed with plausible Mars materials, such as basalts and palagonites (Palomba et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The carbonate occurs within bedrock units showing evidence of erosion. Palomba et al (2009) identified widespread occurrences of magnesium carbonates across large parts of Mars, and including both light and dark regions based on an absorption feature in the 3.9-mm region. The carbonates appear to be present on the surface, as opposed to in airborne dust, and are present at the few wt% level.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an understanding of the link between atmospheric CO 2 levels and greenhouse warming, high levels of CO 2 could support abundant liquid water, thus facilitating rock weathering by carbonic acid to release Ca, Mg, and Fe ions to water and to promote the precipitation of solid carbonates. However, massive carbonate deposits are missing on Mars as inferred from rovers and orbital-based spectroscopic studies (Bandfield et al, 2003;Bullock and Moore, 2007;Palomba et al, 2009). Like CO 2 , atmospheric SO 2 is another greenhouse gas whose complex geochemical cycle includes dissolution into surface waters, acid weathering of surface rocks, and precipitation as a relatively stable solid (Halevy et al, 2007;Johnson et al, 2008;Tian et al, 2010).…”
Section: Mass-independent Oxygen Isotopic Compositions In Solids To Rmentioning
confidence: 99%